1950
DOI: 10.1172/jci102261
|View full text |Cite
|
Sign up to set email alerts
|

THE METABOLISM OF l-TYROSINE IN INFANTILE SCURVY 1

Abstract: Attention has been drawn by Levine, Marples, and Gordon (1) to the relationship between ascorbic acid and the urinary excretion of aromatic amino acid intermediates by the normal premature male infant, both during periods of high protein intake and supplemental tyrosine and phenylalanine ingestion. To our knowledge, no reports have been forthcoming of similar studies with older, ascorbic acid depleted subjects.3 This communication is concerned with the metabolism of l-tyrosine in infantile scurvy. Observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

1951
1951
1975
1975

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Ascorbic acid promptly cured the hydroxyphenyluria in these infants (Levine et al 1939(Levine et al , 1943Woolf & Edmunds, 1950) and it rarely appeared in an infant that had ever been fed with ascorbic acid. Adults or infants suffering from scurvy also showed hydroxyphenyluria when fed with large doses of tyrosine (Rogers & Gardner, 1949;Morris, Harpur & Goldbloom, 1950) and here again feeding with ascorbic acid cured the hydroxyphenyluria. Independently of the above work, Sealock & Silberstein (1939, 1940 had shown that scorbutic guinea pigs developed hydroxyphenyluria if they were fed with tyrosine.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…Ascorbic acid promptly cured the hydroxyphenyluria in these infants (Levine et al 1939(Levine et al , 1943Woolf & Edmunds, 1950) and it rarely appeared in an infant that had ever been fed with ascorbic acid. Adults or infants suffering from scurvy also showed hydroxyphenyluria when fed with large doses of tyrosine (Rogers & Gardner, 1949;Morris, Harpur & Goldbloom, 1950) and here again feeding with ascorbic acid cured the hydroxyphenyluria. Independently of the above work, Sealock & Silberstein (1939, 1940 had shown that scorbutic guinea pigs developed hydroxyphenyluria if they were fed with tyrosine.…”
mentioning
confidence: 79%
“…None of the mothers showed signs of ascorbic acid deficiency during pregnancy, and seven of them took supplementary ascorbic acid. It seems improbable that these infants lacked ascorbic acid, and in any case deficiency of this vitamin will not produce hydroxyphenyluria unless the premature infant or scorbutic infant or adult is also given a high-protein diet or a 'loading' dose of phenylalanine or tyrosine (Levine et al 1939(Levine et al , 1943Woolf & Edmunds, 1950;Rogers & Gardner, 1949;Morris et al 1950).…”
mentioning
confidence: 99%
“…p-Hydroxyphenylpyruvic acid occurs in the urine of infants fed large doses of tyrosine or phenylalanine (Levine, Marples, andGordon, 1939, 1941 ;Levine, Dann, and Marples, 1943;Woolf and Edmunds, 1950), of sufferers from scurvy (Rogers and Gardner, 1949;Morris, Harpur, and Goldbloom, 1950), of adults and children with hepatic cirrhosis (Felix, Leonhardi, and Glasenapp, 1951 ;Woolf, unpublished), and, as briefly reported above, of a number of normal infants (Gibbs and Woolf, in preparation). It is difficult to distinguish p-hydroxyphenylpyruvic acid from phenylpyruvic acid by using ferric chloride or 2:4-dinitrophenylhydrazine; the two acids can be differentiated by using phenistix and observing the colour on the strip, but not if the reagents on the strip are leached out into the urine.…”
Section: Mental-deficiency Surveymentioning
confidence: 86%
“…It has been reported that scorbutic subjects given a load of L-tyrosine excrete large amounts of tyrosine and its metabolites-a defect that is eliminated by administration of ascorbic acid (Rogers and Gardner, 1949a, b;Morris, Harpur, and Goldbloom, 1950;Huisman and Jonxis, 1957;Mohanram and Reddy, 1974). A transient defect in tyrosine oxidation has also been commonly observed in preterm infants fed on high protein diets (Levine, Marples, and Gordon, 1939;Levine, Gordon, and Marples, 1941;Matthews and Partington, 1964;Rizzardini and Abeliuk, 1971;Prasad, Sinha, and Sen, 1972).…”
mentioning
confidence: 99%